Alfalfa silages and hay and corn supplementation for yearling steers - Bolsen, K.; Ilg, H.; Hinds, M.; Hoover, J. (Kansas State University. Agricultural Experiment Station, 2011)
Four alfalfa forages were evaluated: 1) hay; 2) low-dry matter (DM) silage; 3) medium-DM silage; and 4) high-DM silage. All forages were full-fed along with 2 lb of supplement or supplement plus 2 or 4 lb of cracked corn. Calves fed hay or medium-DM silage had the fastest and most efficient gains. Hay had the highest intake; low-DM silage, the lowest. Adding corn to the ration improved calf performance slightly, but feed costs per lb of gain were similar for all three levels of corn supplementation. Low- and medium-DM silages were better preserved than high-DM silage, which contained considerable spoilage due to yeasts and molds. High-DM silage also had the highest ensiling temperatures and it was slightly less stable in air on feedout than was either of the other two silages. Dry matter recovery from the stave silos, however, was about 3 percentage units greater for the high-DM silage than for the low- or medium-DM silages.
Keywords: Beef; Alfalfa silages; Hay; Corn; Steers; Dry matter